Diverse cultivation strategies are necessary to capture microbial diversity in High Arctic lake sediment - Berdy, Brittany M.; Williams, Claire E.; Sizova, Maria; Jung, Dawoon; Tandogan, Nil; Goluch, Edgar D.; Epstein, Slava (Frontiers in Microbiomes, 2025)
While metagenomics has revolutionized our understanding of microbial diversity and function, the cultivation of microorganisms remains indispensable for elucidating their physiological characteristics and potential biotechnological applications. Cultivation provides context to the vast metagenomic datasets and helps verify metagenome-based hypotheses on microbial interactions. The majority of microorganisms remain uncultivated, and this is particularly prominent from extreme environments such as the Arctic. Here we aimed to contribute to the growing body of work investigating microbial ecology in extreme environments by assessing the efficacy of a variety of cultivation approaches in lake sediment in the High Arctic. To try and capture the full breadth of organisms present, we used standard, in situ, and anoxic cultivation methods. We cultured a total of 1,109 microorganisms which clustered into 155 OTUs (97% rRNA gene sequence similarity), representing organisms from Proteobacteria, Actinobacteria, Bacteroidota, and Firmicutes. Importantly, no single method of cultivation proved to be sufficient to represent the cultivable organisms within the environment. Rather, each method resulted in many unique OTUs. Therefore, multiple approaches should be used in conjunction to access the bulk of microbial taxa in a given environment.